Are oxidative stress markers helpful for diagnosing the disease and determining its complexity or extent in patients with stable coronary artery disease? - Mustafa Yılmaz; Cihan Altın; Afag Özyıldız; Haldun Müderrisoğlu (KARE Publishing, 2017)
Objective: The aim of this study was to investigate the relationship between oxidative/antioxidative stress markers and the diagnosis and complexity of coronary artery disease (CAD) in patients with stable CAD. Methods: A total of 145 patients were enrolled in the study. Based on coronary angiography results, the patients were categorized into 2 groups: those without CAD (Group 1) and those with CAD (Group 2). The patients in Group 2 were also categorized into low score and moderate/high score groups according to their SYNTAX score. The serum malondialdehyde (MDA) and total antioxidant capacity (TAOC) levels of Group 1 and Group 2 were compared. Finally, MDA and TAOC levels were compared between the moderate/high-risk and low-risk groups formed according to SYNTAX score. Results: There was a significant difference with respect to both serum TAOC and MDA levels between Group 1 and Group 2 (p=0.036 and p=0.029, respectively). The groups with a SYNTAX score 1-22 and with a SYNTAX score >22 were not significantly different with respect to serum TAOC or MDA level (p=0.582 and p=0.85, respectively). Conclusion: The serum MDA level was significantly higher and the TAOC level was significantly lower in patients with stable CAD compared to those without; however, these molecule levels failed to predict disease complexity in patients with stable CAD.